Capital adequacy regulation - Siddika, Aysa; Haron, Razali (IntechOpen, 2020)
This chapter aims to provide a concise overview of the capital adequacy regulation, importance of the regulation, and evolution of the capital adequacy regulation. Bank capital executes the significant role of preventing the bank from failure and acts as a buffer against possible losses. Capital adequacy is the least amount of capital a bank has to preserve to execute the business, take advantage of profitable growth opportunities, absorb losses, and sustain the customers’ confidence on it. Several bank crises and bank defaults motivate the Basel Committee on Banking Supervision to provide a comprehensive guideline in managing bank capital. The capital adequacy regulation is an international standard to safeguard the banks through setting a risk-sensitive minimum capital requirement. The regulatory authority sets the regulatory capital, and the operating banks are required to maintain the adequate level of capital.